Application of Conversational Intelligent Reporting System Based on Artificial Intelligence and Large Language Models - Zhou, Hong; Xu, Kangming; Bao, Qiaozhi; Lou, Yan; Qian, Wenpin (Journal of Theory and Practice of Engineering Science, 2024)
As large language models gain traction in the financial sector, they are revolutionizing the workflows of financial professionals. From data analysis and market forecasting to risk assessment and customer management, these models demonstrate significant potential and value. By automating data processing tasks, they enhance productivity and empower professionals to derive deeper insights and make more precise decisions. This article explores the application of conversational intelligent reporting systems, leveraging artificial intelligence and large language models, within the financial industry. It examines how these systems streamline reporting processes, facilitate efficient communication, and contribute to informed decision-making, ultimately reshaping the landscape of financial market operations.